The roles of women in Malay families in the Semerah Padi squatment / Wee Chong Hui (Universiti Teknologi MARA, Sarawak, 1996)
Women formed half of the Malaysian population (Department of Statistics, 1991). With 48 per cent of them in the working age group of 15-65 years, however, they formed only one third of the labour force. Their labour participation rate was low. For instance, in 1993, their participation rate was 41.9 per cent compared to 83.8 per cent for men (Department of Statistics, Malaysia, 1994). Notwithstanding their low labour participation, the scenerio is changing. Their participation rate had been increasing from 37.2 per cent in 1970 to 45.8 per cent in 1990 and 47.5 per cent in 1995 {Seventh Malaysia Plan). Besides, Malaysian women, according to the Second World Conference on Women in Nairobi, were reported to have enjoyed equal pay in most sectors as well as separate tax assessment from that of their husbands. Furthermore, in the Fourth World Conference on Women in Beijing in 1995, it was reported that Malaysia would be committed to a 30 per cent target for women in decision-making positions in the political, public and private sectors (New Straits Times, 26 August, 1996). However, the majority of women are less active in the labour force compared to men. There are also regional differences. In Sarawak, for example, the participation for women in 1991 was only 37.7 per cent compared to the national rate of 46.9 per cent. More significantly, a recent study found that the labour participation rate for urban squatter women in Kuching was a mere 10.49 per cent (Wee, Jennifer, Rosziati and Sim, 1995).